Synthesis of nitrogen-doped graphene coupled acid fuchsin photocatalyst turns aryl-vinyl into aromatic aldehydes under visible light - Manish; Yadav R.K.; Singh S.; Shahin R.; Singh C.; Nayak R.R.; Singh A.P.; Tiwary D.; Kumar P.; Baeg J.O.; Gupta N.K. (My University, 2025)
A schematic strategy is presented to overcome the problem of low photocatalytic performance of graphene. Herein, we synthesized nitrogen-doped graphene (NDG)-coupled acid fuchsin (AF) photocatalyst, i.e.; NDGCAF photocatalyst. The NDGCAF photocatalyst has excellent solar light harvesting ability, band gap suitability, and high molar extinction coefficient than the NDG photocatalyst. Due to these properties, the NDGCAF photocatalyst has the ability to oxidize aryl-vinyl into aryl-vinyl-aldehyde under the irradiation of visible light. In this context, it exhibited the utmost conversion efficiency of aryl-vinyl to aryl-vinyl-aldehyde with a good yield of 98.15%. Current research highlights the significant application of NDGCAF light-harvesting photocatalysts in the research field of organic transformations. © 2024 - IOS Press. All rights reserved.